2011
DOI: 10.1007/s10593-011-0696-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclocondensation of 2-iodobenzaldehyde with benzamidines catalyzed by copper(I) iodide: a route to 2-arylquinazolines

Abstract: The reaction of benzamidines with 2-bromo-and 2-iodobenzaldehydes catalyzed by the CuI/L-proline system has been studied. Reaction with 2-iodobenzaldehyde leads to the formation of quinazolines in good yield. 2-Bromobenzaldehyde forms 2-arylquinazolines in low yield due to the competing reaction involving two molecules of amidine leading to a dihydrotriazine.Keywords: benzamidine, 2-iodobenzaldehyde, quinazoline, catalysis by copper(I).Up to the present many efficient methods have been developed for the N-aryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…using o ‐iodobenzaldehydes 158 reacted with benzamidines 159 in this synthetic methodology can yield quinazoline 160 (Scheme 56). [204] …”
Section: Quinazolinesmentioning
confidence: 99%
See 1 more Smart Citation
“…using o ‐iodobenzaldehydes 158 reacted with benzamidines 159 in this synthetic methodology can yield quinazoline 160 (Scheme 56). [204] …”
Section: Quinazolinesmentioning
confidence: 99%
“…Lobanov et al using o-iodobenzaldehydes 158 reacted with benzamidines 159 in this synthetic methodology can yield quinazoline 160 (Scheme 56). [204] Beifuss et al effectively demonstrated the feasibility of utilizing 2-bromobenzyl bromides 161 as substrates through the inclusion of DMEDA as an additive (Scheme 57). [205] The use of water as a solvent in the reaction yielded satisfactory results, with Cu 2 O displaying exceptional catalytic efficiency under these circumstances.…”
Section: Formal [3 + 3] Reactionmentioning
confidence: 99%
“…Further,t hey are limited by 1) the use of toxic solvents such as DMF and DMSO,2 )the need for al ong reactiont ime, and 3) poor yields. [21,22] We chose 2-bromobenzaldehyde (1a)a nd benzamidine hydrochloride (2a)a sm odel substrates, and the reactionw as performed in the presence of the Cu 2 On anocatalyst, base, and solventb yu sing ad omestic microwave for 4min. The tandem cyclization of 1a with 2a in the presence of 5mol %C u 2 O nanocatalyst and 2.0 equivalents of Cs 2 CO 3 in EG at 160 W( domestic microwave) for 4min furnished 2-phenylquinazoline (3aa)in51% yield ( Table 1, entry 1).…”
Section: Evaluation Of the Catalytica Ctivity Of Cu 2 Onanocubesmentioning
confidence: 99%